Ointment Formulation and Test Safety from Sapodilla Manila Leaf Extract (Manilkara zapota L.) with Variation of Ointment Base as an Ulcer Medicine - Imas Maesaroh; Daniar Pratiwi; Leli Agustin (Indonesian Journal of Pharmaceutics, 2020)
Leaf extract of Manilkara zapota L has antibacterial activity against Staphylococcus aureus at a  base on potency test of 50%, where the bacteria are the cause of boils. Some of effort to facilitate the use and increase the activity of active substances, then ointments are prepared on a variety of ointment bases. This study aims to prepared Manilkara zapota L leaf extract into ointment formulations, and chosed the best of ointment base formulations that meets the requirements standards for good ointment preparations. The extract was obtained by maceration using ethanol 96%. Ointments are formulated with four different types of ointment bases, which are hydrocarbon base, absorbing base, water removed bases, and water soluble base. The ointment that has been produced is tested for the physical characteristics such as organoleptic test, homogeneity, pH, spreadibility, adhesion, and viscosity had been tested on manufactured ointments. The results of this study indicate that leaf extract of Manilkara zapota L can be formulated into ointment preparations, variations in the ointment base affect the physical characteristics of ointment preparations.Keywords: Ointment, Manilkara zapota L Leaf, Antibacterial, Staphylococcus aureus